2013
DOI: 10.1111/tbj.12101
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Distribution and Internal Enhancement Architecture of Contrast-Enhanced Magnetic Resonance Imaging in the Diagnosis of Non-Mass-Like Breast Lesions: A Meta-Analysis

Abstract: The aim of this study is to assess the diagnostic performance of contrast-enhanced magnetic resonance (MR) imaging in patients with non-mass-like breast lesions in a meta-analysis. Literature study was performed on PubMed data base on the diagnostic performance of MR imaging in patients with non-mass-like breast lesions. Details of the relevant studies were reviewed and a meta-analysis was performed to estimate the overall sensitivity and specificity of contrast-enhanced MR imaging of non-mass-like breast lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
12
3
2
Order By: Relevance
“…Furthermore, the studies evaluating mass lesions had a higher SPE (0.884) than those evaluating non-mass-like breast lesions (0.70). A recent meta-analysis found higher SPE and lower SEN values for DCE-MRI of 0.80 (95% CI ¼ 0.77-0.83) and 0.50 (95% CI ¼ 0.46-0.53), respectively (37), than in the present meta-analysis. With the combination of DCE-MRI and DWI, it might be possible to avoid unnecessary surgery or biopsy procedures for benign lesions or inadequate observation of malignancy when non-mass-like lesions are encountered on breast MRI.…”
Section: Discussioncontrasting
confidence: 85%
“…Furthermore, the studies evaluating mass lesions had a higher SPE (0.884) than those evaluating non-mass-like breast lesions (0.70). A recent meta-analysis found higher SPE and lower SEN values for DCE-MRI of 0.80 (95% CI ¼ 0.77-0.83) and 0.50 (95% CI ¼ 0.46-0.53), respectively (37), than in the present meta-analysis. With the combination of DCE-MRI and DWI, it might be possible to avoid unnecessary surgery or biopsy procedures for benign lesions or inadequate observation of malignancy when non-mass-like lesions are encountered on breast MRI.…”
Section: Discussioncontrasting
confidence: 85%
“…For ROC analysis, Z.Z.S et al performed a metaanalysis of diagnostic performance based on morphological characteristics and enhanced parameters by using pooled weighted estimates, and their results indicated low sensitivity (50%) and high (80%) speci city. In contrast, the results of this study indicated high sensitivity (80.6%), while the speci city was not high (72.5%) [24].…”
Section: Discussioncontrasting
confidence: 96%
“…The malignant potential of additional NME lesions should be elucidated because their malignant behavior can alter the course of treatment. Although several studies have characterized the MRI features of NME in differentiating malignant and benign lesions ( 6 , 7 , 11 - 17 , 19 - 25 ), standardized interpretative criteria based on the BI-RADS MRI lexicon for NME do not exist. Our study focused on additional NME lesions identified during preoperative MRI, a scenario occasionally encountered in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%